Rapid remediation of Cd(II)-contaminated water using a magnetically collectable iron-based primary battery. Issue 2 (April 2022) - Guo, Xinyue; Hu, Yanqiu; Chen, Chaowen; Zhang, Jia; Yang, Pengqi; Du, Yue; Wang, Dongfang; Cai, Dongqing; Wu, Zhengyan
Abstract: Remediation of cadmium ion in polluted water suffers from high cost and low efficiency. Nanoscale zero-valent iron (NZVI) was able to extract Cd(II) from water effectively, but the liability to aggregate greatly limits its broad application. Herein, we develop a promising remedy (CCP@NZVI) for the rapid and efficient removal of Cd(II) in water by facile coating conductive carbon paint (CCP) on NZVI. Compared with NZVI alone, CCP@NZVI shows enhanced efficiency, achieving removal up to 95% in 5 min at a low dose (0.67 g/L). We demonstrated the validity of a build-in primary battery as the driving force for the removal of Cd(II). In water contaminated by Cd(II), NZVI acting as the anode tends to be oxidized to ferrous ion and transfers electron to CCP as the cathode, wherein dissolved O2 is reduced to OH - for interfacial Cd(II) precipitation. A panel of characterization techniques including scanning electron microscopy, X-ray photoelectron spectroscopy, X-ray powder diffraction, and open circuit potential, have been used to analyze CCP@NZVI before and after the reactions, verifying the immobilization of absorbed Cd(II) in CCP@NZVI as Cd(OH)2 . In addition, this method exhibits good stability against weak acid and coexisting anions with satisfactory biosafety. Importantly, the Cd-immobilized CCP@NZVI after treatment can be easily separated via weak magnetic field. This study provides a novel strategy to achieve rapid Cd(II) removal at low-cost and with collectability, which may have a tremendous application prospect in environment fields including water treatment and soil detoxication. Graphical Abstract: ga1 Highlights: A primary battery nanosystem was fabricated. Core-shell structured CCP@NZVI consists of NZVI and conductive carbon paint (CCP). CCP@NZVI could effectively remove Cd(II) from water rapidly. CCP@NZVI after treatment can be readily separated from water by magnet. CCP@NZVI possessed a good biosafety.